The Iliad in a nutshell : visualizing epic on the Tabulae Iliacae - Squire, Michael (Oxford University Press, 2011)
The Tabulae Iliacae (Iliac tablets) are a collection of 22 miniature marble reliefs from the early Roman Empire; all of them are inscribed in Greek, and most depict the panoramic vistas of Greek Epic. This book brings the tablets to life as never before, revealing the unassuming fragments as among the most sophisticated objects to survive from the ancient Mediterranean world. The Iliad in a Nutshell is not only the first monograph on this material in English (accompanied by a host of new photographs, diagrams, and reconstructions), it also examines the larger cultural and intellectual stakes--both in classical antiquity and beyond.